An analysis of W.A. Mozart’s Sonata No. 18 in D Major, K.576, F. Schubert’s Drei Klavierstücke No. 2, D.946, F. Chopin’s Ballade No. 1 in G minor, Op. 23, A. Scriabin’s Prelude and Nocturne Op. 9, N. Kapustin’s Concert Etudes Op. 40, Nos. 1 & 5, L. Vierne’s Carillon de Westminster Op. 54 No. 6: theoretic, stylistic and historical background - Dredger, Mary Margaret (Kansas State University, 2022)
The purpose of this manuscript is to supply extended program notes for a master’s recital performed in partial fulfillment of a master’s degree in April 2022. The pieces under discussion are W.A. Mozart’s Sonata No. 18 in D Major, K.576, F. Schubert’s Drei Klavierstücke No. 2, D.946, F. Chopin’s Ballade No. 1 in G minor, Op. 23, A. Scriabin’s Prelude and Nocturne Op. 9, N. Kapustin’s Concert Etudes Op. 40, Nos. 1 & 5, and L. Vierne’s Carillon de Westminster Op. 54 No. 6. Included are full analyses of each piece performed, biographical information on each composer, and brief interpretive and performance-oriented suggestions.
Keywords: Piano; Analysis; History; Performance